Analyzing Financial Ratios as Indicators to Measure Financial Performance at PT. Industri Jamu dan Farmasi Sido Muncul Tbk - Zada Annuri Nabila; Cinta Rizkia Zahra Lubis; Maulana Rizqy Efvarius; Selvia Apriani; Sabda Dian Nurani Siahaan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the financial performance of PT. Industri Jamu Dan Farmasi Sido Muncul Tbk from 2020-2022 using financial ratio analysis. The financial ratio analysis used includes liquidity, solvency, profitability, and activity ratios. This research uses a descriptive analysis method with a quantitative approach. The outcomes demonstrated that the firm's financial performance as measured by the liquidity ratio was stable., except for inventory to net working capital with an average of 0.26. The solvency ratio is also declared solvable. The condition of the company based on the profitability ratio is not good and the company must take action. The average activity ratio is healthy, except for asset turover with an average of 0,93.